Self-seal laser ablation open cell for trace elements analysis of full-size archaeological artefacts: application on Famille Rose enamel - Delbey, Thomas; Norris, Dana; Douglas, David; Shortland, Andrew J. (Elsevier, 2024)
Laser Ablation Inductively Coupled Plasma Mass Spectrometry (LA-ICP-MS) is a technique that is increasingly becoming the standard analytical approach in archaeological science, especially for the analysis of glass, glaze, and metal. Its low detection limits, high precision and wide element range is twinned with a very small sample size, which makes it ideal for culturally valuable objects. However, in the past, the small sample chamber size in commercial laser systems has meant that the size of object that could be analysed is very limited. Ongoing work by various groups has demonstrated the potential of open architecture and portable systems to overcome this issue. This paper reports an example of this − the results of a validation on a self-seal open ablation cell coupled with a very large sample chamber developed by Cranfield University and Elemental Scientific Lasers LLC. Comparison of the analysis of standard reference materials between the self-seal open cell and a conventional closed cell in a two-volume chamber show that, the count rates for most elements drop in the open cell to between 40–70% with our configuration, but precision, accuracy, fractionation, and limits of detection are barely affected. This means that the result outputs of both chambers are very similar and shows that the open cell is a very real solution to the problem of the small sample chambers in conventional LA-ICP-MS facilities. The functionality of the open cell is demonstrated using a case study of two Chinese, polychrome enamelled copperwares dating from the late 18th or early 19th century Qianlong or Jiaqing period, a tray and a writing set. Due to conservation work on the pieces, five small enamel samples were available, which meant that the results derived from these samples in the conventional laser chamber could be compared to results from the objects themselves in the large sample chamber. Time resolved analysis was carried out giving more information on the thickness of enamel layers and variability between colours and across the object demonstrating the usefulness of having large, complete objects in the chamber.
Keywords: LA-ICP-MS; Archaeological science; Chinese enamel; 34 Chemical Sciences; Analytical Chemistry